The role of CMV in glioblastoma and implications for immunotherapeutic strategies - Rahman, Maryam (Oncoimmunology, 2018)
Controversy surrounds the role of cytomegalovirus (CMV) in glioblastoma (GBM). However, several studies have shown that CMV nucleic acids and proteins are present within GBM tumor tissue. CMV has been implicated in GBM pathogenesis by affecting tumor stem cell factors, angiogenesis and immune pathways. Anti-viral therapy has not been found to definitively improve outcomes for patients with GBM. Several studies have leveraged CMV by targeting CMV antigens using ex-vivo expanded T cells or dendritic cell vaccines. The initial results from these studies are promising and larger studies are underway.